Providing Health Counseling on Stunting to Young People in Dusun II Pekik Nyaring, Pondok Kelapa Sub-district, Central Bengkulu Regency - Utomo, Meto Widio; Wilantara, Anggi; Khairunnisa , Miska (Universitas Dehasen Bengkulu, 2024)
Stunting is a disruption in the growth and development of children due to long-term malnutrition. Stunting can be caused by malnutrition experienced by the mother during pregnancy, or by the child during his growth period. The main programs that we have compiled can be carried out well and smoothly with the support, assistance and participation of the government and the people of Pekik Nyaring Village, Central Bengkulu Regency and all those who have helped our KKN program